MOBILITAS MATA PENCAHARIAN MASYARAKAT PESISIR SUNGAI ROKAN DESA RIMBA MELINTANG KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Muhammad Khofli; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Background of this research is derived from the writer observation of the livelihood mobility of the coastal communities of the river Rokan of Rimba Melintang district Rimba Melintang of Rokan Hilir. The formulation of problems from this research is what are the driving factors and attractors of the livelihoods of coastal communities and how is the vertical mobility that occurs in transverse village communities. The population of this research were people who used to work as traditional fishermen who did livelihood mobility after being moved to their new place and By used census techniques, samples are obtained by taking 50% of the entire population in Rimba Melintang and found as big as 45 respondents with homogeneous communities. For example, the data analysis used descriptive quantitative method. The results of this study showed that out of 45 respondents, they had moved to become laborers of oil palm farmers, construction workers, farmers, traders, entrepreneurs, artisans and odd jobs. This livelihood mobility is driven by factors of coastal environment damage due to the construction of plaster which is forced to be moved by the downstream government to a new place. This makes them have to do livelihood mobility supported by some of their pulling factors which are economic factors. Not all respondents experienced changes except 80% of respondents improved their lives, which occurred in the form of changes in the forms of livelihoods found to changed income and ownership of assets and so on. In other words, 60% of these respondents experienced vertical upward mobility while others experienced a downward vertical mobility and horizontal mobility.Keywords: The Mobility of livelihood, Coastal Cumminities,, Rimba Melintang District.